METODE PENENTUAN TITIK KOORDINAT ZONA POTENSI PENANGKAPAN IKAN PELAGIS BERDASARKAN HASIL DETEKSI TERMAL FRONT SUHU PERMUKAAN LAUT - Hamzah, Rossi; Prayogo, Teguh; Marpaung, Sartono (Institut Teknologi Sepuluh Nopember, 2016)
Information points coordinate of potential fishing zones (PFZ) is required by user that to be more effective in conducting fishing operation. The results of thermal front detection using single image edge detection (SIED) as shape contour lines. This research aims to determine points coordinate for potential fishing zone based on detection of thermal fronts sea surface temperatures. To determine point coordinate performed segmentation on detection result according to size fishnet grid. Contour line contained in each grid is a polygon shape. Centroid of each polygon is point coordinate of PFZ. The result of sea surface temperature data processing from Terra/Aqua MODIS and Suomi NPP VIIRS satellite indicates that method of determination the centroid of polygon is very effective in determining the point coordinate of PFZ. Using that method the processing stages of satellite data to be faster, more efficient and practical due to the information of PFZ is already as points coordinate.